Biological invasions via ballast water: evaluating the distribution and gaps in research effort by geography, taxonomic group, and habitat type - Costa-Areglado, Flávia M. P.; Ruiz, Gregory M.; Brandini, Frederico P. (Frontiers in Marine Science, 2025)
While crucial for maneuverability and safety of commercial ships, ballast water (BW) has long served as a major vector for the distribution of non-native species in coastal ecosystems. Species transfers via shipping can alter community composition, ecosystem function, economies, and human health. In recent decades, a significant body of research has focused on BW, including many in-situ studies, but this is unevenly distributed across global regions. Here, we conducted a literature review to evaluate the distribution of published BW studies across geographic regions, taxonomic groups, and habitats, highlighting some current knowledge gaps. Of 2,088 publications on BW in our review, 270 (13%) reported on in-situ sampling from ballast tanks across 194 unique geographic locations. For both number of publications and sampling effort, approximately 85% were from the northern hemisphere. Considering planktonic organisms sampled in BW, only 12% of publications were from the southern hemisphere, and no study reported analyses of benthic communities in ballast tanks outside of North America and Europe. While we recognize that our review does not capture all existing data, such as technical reports and regional journals, it provides a relative measure of research effort to date, highlighting the disparity among regions in taxonomic and habitat analyses of ballast communities. In particular, the low frequency of in-situ measures for many regions (especially the southern hemisphere) limits current understanding of BW species transfers, including changes over time in response to evolving management and policy across the globe.